Correction: Quantum curcumin mediated inhibition of gingipains and mixed-biofilm of Porphyromonas gingivalis causing chronic periodontitis(RSC Advances (2018) 8 (40426–40445) DOI: 10.1039/C8RA08435A) - Singh A.K.; Yadav S.; Sharma K.; Firdaus Z.; Aditi P.; Neogi K.; Bansal M.; Gupta M.K.; Shanker A.; Singh R.K.; Prakash P. (My University, 2025)
The authors regret the incorrect naming of the bacterial species Actinomycetemcomitans viscosus in the published article. It should be correctly shown as Actinomyces viscosus throughout, on pages 40427 (fifth line of last paragraph), 40436 (sixth line of “Individual isolates & mixed” section), 40437 (Table 2) and 40440 (Table 3). Also, the ATCC number of A. viscosus was incorrectly given as 29522 throughout the published article and should be correctly shown as 15987 in the following places: p. 40429 (“Bacterial strains and culture conditions” section and “Minimum inhibitory concentration determination” section), p. 40430 (“Determination of antibiofilm activity using tissue culture plate assay (TCP)” section), p. 40434 (“Antimicrobial assay of quantum curcumin against clinical isolates of Porphyromonas gingivalis and select reference strains” section and “Determination of minimum inhibitory concentration” section), p. 40435 (“Growth rate analysis” section), p. 40437 (Table 2), and on p. 40438 (caption to Fig. 7 (twice), caption to Fig. 8, and sixth line of “Discussion” section). An error was also present in the published article in the co-author name spelling for K. Sharma. The correct spelling of the author names is as shown here. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers. © The Royal Society of Chemistry.